2011
DOI: 10.1172/jci42874
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide inhibits human cancer cell growth and tumor development in mice by blocking Hedgehog/GLI pathway

Abstract: The Hedgehog (Hh) pathway is activated in some human cancers, including medulloblastoma. The gliomaassociated oncogene homolog (GLI) transcription factors are critical mediators of the activated Hh pathway, and their expression may be elevated in some tumors independent of upstream Hh signaling. Thus, therapies targeting GLI transcription factors may benefit a wide spectrum of patients with mutations at different nodal points of the Hh pathway. In this study, we present evidence that arsenic trioxide (ATO) sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
295
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(305 citation statements)
references
References 56 publications
(67 reference statements)
9
295
0
1
Order By: Relevance
“…As 2 O 3 has good curative effects and little cross-resistance with conventional chemotherapeutics (2,(17)(18)(19)(20)(21). Previous studies have revealed that conventional MDR leukemia cells exhibit increased sensitivity to As 2 O 3 instead of manifesting cross-resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As 2 O 3 has good curative effects and little cross-resistance with conventional chemotherapeutics (2,(17)(18)(19)(20)(21). Previous studies have revealed that conventional MDR leukemia cells exhibit increased sensitivity to As 2 O 3 instead of manifesting cross-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation for this is that As 2 O 3 may not be a substrate of P-gp and may inhibit P-gp activity (2,(18)(19)(20)(21)(22). The present study selected HL-60 human promyelocyte leukemia cells for doxorubicin (ADM)-resistance by long-term exposure to intermittent and continuous stepwise increments of ADM, and characterized the distinguishing features of acquired MDR, particularly in terms of sensitivity to As 2 O 3 and the role of LSCs.…”
Section: Cd117mentioning
confidence: 99%
“…Further observations corroborate this finding; for instance, treatment of Ewing sarcoma family of tumors (ESFT) cell lines with ATO led to marked cytotoxicity and the presence of higher GLI1/2 expression seems to indicate increased sensitivity to ATO. Additionally, tumor growth in ESFT xenografts was inhibited with ATO administration; this treatment was associated with an increased survival in constitutively activated SMO transgenic mouse model for medulloblastoma (ND2:SmoA1), with significantly decreased GLI target gene expression [82].…”
Section: Hh Inhibitors Antagonizing Components Downstream To Smomentioning
confidence: 99%
“…Itraconazole, also inhibits Shh signaling by inhibiting downstream gli-2 transcription, such as ATO and darinaparsin, (16). In a phase II study, itraconazole showed only modest antitumor activity, and dose escalation was limited by toxicity (15).…”
Section: Discussionmentioning
confidence: 99%